Practicum Evaluation: Developing Instrument of Scientific Attitudes in Biology - Inayah, Ardina Dwi Yani; Harahap, Lia Junita (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Practicum is an important part that is very closely related to biology. To test theory or find theory need practicum. The practicum can run smoothly and the results of activity practicum can be achieved with a maximum of one of them the factor is if the student's attitude is scientific. This study aims to develop an attitude instrument scientific on activities valid and reliable practicum. The method used in this research is Research and Development (RD) with the ADDIE model. Stages include Analysis, Design, Development, Implementation, and Evaluation. The results of the study indicate that the scientific attitude instrument is feasible to use because the expert validation result is 86.88. The empirical validation results show that there are 38 valid statements because it is more than 0.3338 and the reliability is more than 0.6.Keywords: Biology, Instrument, Practicum, Scientific Attitude